5G Fronthaul in Modular P4: eCPRI Protocol Processing and Precise BMv2 Timestamps for PTP-1588 - Atabak Nojavan; Bill Pontikakis; Francois-Raymond Boyer; Yvon Savaria (IEEE Access)
P4, a domain-specific language (DSL) for programming network devices, offers flexibility in defining packet processing behaviors. This paper demonstrates the use of P4 to achieve modular eCPRI protocol processing and enhanced PTP-1588 synchronization, both critical for 5G fronthaul applications in Open Radio Access Network (O-RAN) environments. By implementing an eCPRI packet processing unit based on the eCPRI Specification Version 2 and inspired by Intel’s FPGA-based IP, we enable modular addition of new message types and custom packet processing functionality in P4. Our approach reduced lines of code per type by 85% and decreased configuration time by up to 5x compared to traditional methods, significantly simplifying complexity. Additionally, we introduce precise ingress and automatic egress timestamps for the BMv2 software switch to improve PTP-1588 accuracy, reducing error margins from 24,000 microseconds to 60 microseconds (99.75% improvement) and achieving sub-microsecond precision. Extensive testing in a Mininet environment validates these improvements, demonstrating enhanced precision and flexibility in handling time-sensitive protocols. While this paper focuses on 5G fronthaul applications in O-RAN networks, the techniques and results presented are equally applicable to other use cases across end-to-end 5G networks and beyond, paving the way for modular, high-precision, and programmable solutions in future open and interoperable network architectures.